The murky waters of neoliberal marketization and commodification on the education of adults in the United States - Zacharakis, Jeffrey; Holloway-Libell, Jessica (My University, 2016)
We approach marketization and commodification of adult education from multiple lenses including our personal narratives and neoliberalism juxtaposed against the educational philosophy of the Progressive Period. We argue that adult education occurs in many arenas including the public spaces found in social movements, community-based organizations, and government sponsored programs designed to engage and give voice to all citizens toward building a stronger civil society. We conclude that only when adult education is viewed from the university lens, where it focuses on the individual and not the public good, does it succumb to neoliberal forces.
Citation: Zacharakis, J., & Holloway, J. (2016). The murky waters of neoliberal marketization and commodification on the education of adults in the United States. European Journal for Research on the Education and Learning of Adults, 7(2), 223-236. doi:10.3384/rela.2000-7426.rela9083
Keywords: Adult Education; Academic Capitalism; Neoliberalism; Marketization; Commodification; Progressive Education